2004
DOI: 10.1227/01.neu.0000137660.06337.c5
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Decompression for Trigeminal Neuralgia in the Elderly: A Review of the Safety and Efficacy

Abstract: MVD is underused in the elderly despite being both safe and effective. Fitness and not age should be the key in deciding the treatment options. It is proposed that any patient with medically refractory TN who is fit for general anesthesia should be given the opportunity to choose MVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
64
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(72 citation statements)
references
References 53 publications
2
64
1
5
Order By: Relevance
“…There is no evidence in the literature to suggest increased major complication rates following MVD that are associated with increasing age. Previous studies have analyzed the results of MVD in elderly patients and demonstrated that the outcomes and morbidity rates are not related to age 2,5) . Broggi et al 5) , along with other physicians, consider MVD in the elderly to be easier and less time-consuming to accomplish than in younger patients, primarily due to brain atrophy and larger cisterns in the former, minimizing retractionrelated complications.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence in the literature to suggest increased major complication rates following MVD that are associated with increasing age. Previous studies have analyzed the results of MVD in elderly patients and demonstrated that the outcomes and morbidity rates are not related to age 2,5) . Broggi et al 5) , along with other physicians, consider MVD in the elderly to be easier and less time-consuming to accomplish than in younger patients, primarily due to brain atrophy and larger cisterns in the former, minimizing retractionrelated complications.…”
Section: Discussionmentioning
confidence: 99%
“…33 It is considered to have the best long-term results for iTN, with a low rate of recurrence of pain (15%-25% within 3 years) 13,23 and few collateral effects. 1,4,[20][21][22]26 The percutaneous balloon compression (BC) of the trigeminal ganglion was introduced by Mullan and Lichtor in 1983. 3,4,32 The recurrence rate after BC is 45.4% in 4 years, 19 and there is a high incidence of masticatory complications 5 and sensory deficits 9,10,29,30 after this procedure.…”
mentioning
confidence: 99%
“…Las publicaciones de Mittal, Taha y cols. (18)(19)(20)(21)(22) consideran que la termocoagulación por radiofrecuencia y la microdescompresión vascular constituyen las variantes quirúrgicas más utilizadas en la actualidad por la alta efectividad, sin hablar de coste-efectividad, lo cual es muy difícil, teniendo en cuenta que las investigaciones relacionadas con el tema no abarcan muchas veces el concepto económico. Muchos dan preferencia a la MDV por la posibilidad de utilizarse en pacientes jóvenes evitando las alteraciones sensitivas que provoca la termocoagulación por radiofrecuencia (23)(24)(25)(26), sin embargo, en el caso de la termocoagulación por radiofrecuencia se considera más beneficiosa, además, es una técnica bien tolerada por los pacientes ancianos, incluso en los menores de 60 años que la prefieren a pesar de los trastornos sensitivos que originan.…”
Section: Discussionunclassified